Concomitant administration of uracil-tegafur and leucovorin during adjuvant radiotherapy for locally advanced rectal cancer - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2007)
Purpose: We report the feasibility and toxicity profile, and the impact on local control, disease-free survival and overall survival rates of our study which consisted of postoperative concurrent chemoradiotherapy, followed by adjuvant chemotherapy using uracil-tegafur (UFT)/leukovorin (L V) in locally advanced rectal cancer patients. Patients and methods: Thirty-one patients operated for rectal adenocarcinoma (pT3/4 or N+) were enrolled onto the study. Twenty-three patients were males and 8 females with median age 62 years (range 21-85). Radiotherapy (RT) to the pelvis with conformal technique and individual blocks was delivered within 8 weeks following surgery. Total RT dose was 50.4 Gy and was given in a conventional single fraction of 1.8 Gyper day. Chemotherapy was administered concomitantly and consisted of UFT(300 mg/m(2)/day) and LV (30 mg/day) during RT-days. Following chemo radio therapy, chemotherapy alone was administered for 4 cycles in the some dose for 28 days every 35 days. Results: No lethal toxicity occurred. All patients completed the scheduled RT. Concurrent chemotherapy continued in 22 (70.9%) patients until the end of RT. Seventeen (54.8%) patients completed the whole concurrent chemoradiotherapy and adjuvant chemotherapy as planned. No grade 3-4 stomatitis/mucositis or haematological toxicities were observed during the whole treatment period. During concomitant therapy grade 1-2 toxicities were: nausea/vomiting 60%, dyspepsia/gastric pain 39%, diarrhea 39% and dysuria 10%, whereas grade 3 nausea and diarrhea occurred in 6% and 19%, respectively. Median follow-up was 22 months. Two-year local control, disease-free survival and overall survival rates were 96.3%, 72.3% and 83.2%, respectively. Conclusion: The acute toxicity profile of UFT/LV local survival and overall survival in the control, disconcurrent chemoradiotherapy setting for operated, locally advanced rectal cancer seem comparable with the standard 5-fluorouracil (5-FU)-based therapies.
Keywords: concomitant chemoradiotherapy; oral fluoropyrimidine; rectal cancer; survival; toxicity; UFT; ORAL LEUCOVORIN; PHASE-III; FLUOROURACIL; CHEMOTHERAPY; THERAPY; UFT; MULTICENTER; TRIAL